Futher study on chemical constituents and biological activities of Alpinia conchigera Griff. (Zingiberaceae) - Tram, Le Huyen; Giang, Phan Minh; Son, Phan Tong (Vietnam Journal of Chemistry, 2014)
β-Sitosterol, stigmasterol, cardamomin (1), chalconaringenin 2′-O-methyl ether (2), alpinetin (3), and naringenin 5-O-methyl ether (4) were isolated from the MeOH extract of Alpinia conchigera Griff. (Zingiberaceae). Their structures were determined on the basis of spectroscopic analyses. The antimicrobial and free radical scavenging activities of the isolates 1-4 were evaluated in correlation with those of the soluble fractions. Key words: Alpinia conchigera; Zingiberaceae; chalcone; flavanone; antimicrobial activity; free radical scavenging activity.